2020
DOI: 10.3390/ijms21186705
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of FZD10 Delivering Exosomes Derived from Colon Cancers Cell Lines in Inducing Activation of Epithelial–Mesenchymal Transition in Normal Colon Epithelial Cell Line

Abstract: Exosomes belong to the family of extracellular vesicles released by every type of cell both in normal and pathological conditions. Growing interest in studies indicates that extracellular vesicles, in particular, the fraction named exosomes containing lipids, proteins and nucleic acid, represent an efficient way to transfer functional cargoes between cells, thus combining all the other cell–cell interaction mechanisms known so far. Only a few decades ago, the involvement of exosomes in the carcinogenesis in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…This mechanism also functions in esophageal squamous cell carcinoma [ 108 ]. In colorectal cancer (CRC), cells with high FZD10 expression were more efficient than cells with low FZD10 at stimulating EMT [ 134 ]. In progression of CRC, FZD10 expression increases from non-dysplastic to dysplastic tissue, suggesting it is activated early in CRC development [ 102 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…This mechanism also functions in esophageal squamous cell carcinoma [ 108 ]. In colorectal cancer (CRC), cells with high FZD10 expression were more efficient than cells with low FZD10 at stimulating EMT [ 134 ]. In progression of CRC, FZD10 expression increases from non-dysplastic to dysplastic tissue, suggesting it is activated early in CRC development [ 102 ].…”
Section: Frizzleds In Cancer Emtmentioning
confidence: 99%
“…Evidence has been reported on a role of exosomes in the promotion of the EMT ( 38 – 41 ). In particular, FZD10-delivering exosomes were also indicated to trigger the EMT in a normal epithelial colon cell line, together with an increase of proteins, such as vimentin and c-Myc, shown to be overexpressed and involved in the mechanisms of cell migration, cell adhesion, and proliferation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has significant implications on cancer progression ( 25 ), and indeed, in the FZD10-mRNA-silenced cells, the viability was restored ( 26 ). We recently reported that activation of the epithelial–mesenchymal transition (EMT) in normal colon epithelial cells (HCEC-1CT) is triggered by FZD10-delivering exosomes extracted from CRC cell lines ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes released from colon cancer cells with high levels of the Wnt receptor frizzled 10 protein (FZD10) can stimulate EMT activation to reprogram normal colonic epithelial cells (Scavo et al, 2020). Cancer stem cell-like cell-derived exosomal lncRNA DOCK9 antisense RNA2 (AS2) can activate the Wnt/β-catenin pathway to induce EMT and promote the progression of papillary thyroid carcinoma (Dai et al, 2020).…”
Section: Primary Epithelial Mesenchymal Transition Signaling Pathwaysmentioning
confidence: 99%